Effects of the hypoxia-inducible factor-1 inhibitor echinomycin on vascular endothelial growth factor production and apoptosis in human ectopic endometriotic stromal cells. (2nd April 2016) - Tsuzuki, Tomoko; Okada, Hidetaka; Shindoh, Hisayuu; Shimoi, Kayo; Nishigaki, Akemi; Kanzaki, Hideharu
Abstract: Recent evidence points to a possible role for hypoxia-inducible factor (HIF)-1 in the pathogenesis and development of endometriosis. The objectives of this study were to investigate the critical role of HIF-1 in endometriosis and the effect of the HIF-1 inhibitor echinomycin on human ectopic endometriotic stromal cells (eESCs). Ectopic endometriotic tissues were obtained from 20 patients, who received an operation for ovarian endometriomas. We examined vascular endothelial growth factor (VEGF) and stromal cell-derived factor-1 (SDF-1) production, HIF-1 expression, cell proliferation and apoptosis of eESCs. Cobalt chloride (CoCl2 ) significantly induced expression of HIF-1α protein and VEGF production in a time-dependent manner in eESCs, but reduced SDF-1 production. VEGF production was significantly suppressed by treatment of 100 nM echinomycin without causing cell toxicity, but 0.1–10 nM echinomycin or 100 nM progestin had no significant effect. SDF-1 production was not affected by echinomycin treatment at any dose. Echinomycin inhibited cell proliferation and induced apoptotic cell death of the eESCs, and significantly inhibited expression of the anti-apoptotic proteins Bcl-2 and Bcl-xL. Echinomycin inhibits VEGF production and induces apoptosis of eESCs by suppression of Bcl-2 and Bcl-xL. These findings suggest the unique therapeutic potential for echinomycin as an inhibitor of HIF-1 activation for endometriosis treatment.